Mapeamento e avaliação de impacto ambiental utilizando aeronave remotamente pilotada no Parque Nacional Serra de Itabaiana - Rodrigues, Jônatas Lemos (2019)
In the state of Sergipe, northeastern Brazil, the only existing federal conservation unit, Serra de Itabaiana National Park (PARNASI), resources are insufficient and limited and have management difficulties. The biggest problems are associated situation about land policy or land use. Several scientific studies conducted indicate the existence of impacts that compromise their ecosystems. The adoption of strategies for acquiring new data on the spatial distribution of land use, the level of existing environmental impact and knowledge sharing is required. In this sense, new technologies, such as small drones, have been presented as possible solutions to help solve conservation problems, and together, information systems can make an important contribution. Up-to-date and inexpensive mapping of land use and land cover in the PARNASI area has been proposed to assess the level of environmental impact as scarce resources, the extent of the park area and its topography pose a management challengeThe potential use of a small drone was evaluated and the level of environmental impact estimated by classifying certain types of uses and correlating them with local slope. The aerial photogrammetry technique was used for data collection and extraction, and the analysis was performed from a multicriteria model where the variables were hierarchized and weighted by assigning a weight for each land use and land cover class. The results show that in 82.2% of the surveyed area were found slope levels considered very weak to medium, thus demonstrating that the mapped area does not have high levels of slope. It is concluded that, although it is an ANAC rated drone for entertainment, embedded technologies such as sensors, actuators, and intelligent flight systems, associated with mission planning and execution systems for aerial photogrammetry, as well as geographic information systems met the research proposals.